Acute exogenous lipoid pneumonia caused by accidental kerosene ingestion in an elderly patient with dementia: A case report. Issue 1 (3rd January 2013) - Gotanda, Hiroshi; Kameyama, Yumi; Yamaguchi, Yasuhiro; Ishii, Masaki; Hanaoka, Yoko; Yamamoto, Hiroshi; Ogawa, Sumito; Iijima, Katsuya; Akishita, Masahiro; Ouchi, Yasuyoshi
<x xml:space="preserve">Abstract</x> Acute exogenous lipoid pneumonia is an uncommon condition caused by aspiration of oil‐based substances, occurring mainly in children. Here, we report the case of an 83‐year‐old patient with Alzheimer's disease who presented with coughing and hypoxia. The diagnosis of acute exogenous lipoid pneumonia caused by accidental kerosene ingestion was made on the basis of the patient's clinical history, and typical radiological and cytological findings. The patient's cognitive impairment and an unsafe environment, in which the patient's 91‐year‐old husband stored kerosene in an old shochu bottle, were responsible for the accidental ingestion. Acute exogenous lipoid pneumonia should be considered in the differential diagnosis for acute respiratory disorders in the rapidly aging population. Geriatr Gerontol Int 2013; 13: 222–225.